Analisis Penentuan Biaya Pokok Produksi Olahan Kopi Robusta di Koperasi Tirto Kencono Kabupaten Tanggamus - Aufa Dian Utami; Zainal Abidin; Lina Marlina (Journal of Food System & Agribusiness, 2019)
This study aims to analyze the basic cost production of processed coffee in Tirto Kencono Cooperative. The method used in this research was the case study. The respondent in this study was the chairman of the cooperative. This research was conducted at Tirto Kencono Cooperative located in Talang 20 Village, Air Naningan District, Tanggamus Regency. The collection data was conducted in March 2019 and analyzed in qualitative and quantitative descriptive.Â  The result showed that the basic cost production used full-costing determination method by using assistance equipment and non-assistance equipment, the result was the cost production of four products using assistance equipment was lower than non-assistance equipment in order to gain higher profit than current selling price.Â  Government assistance had different impacts in terms of the production cost structure particularly the depreciated cost of using assistance equipment which had a percentage of 0,80% and non-assistance equipment of 1,20%.